A human embryonic stem cell reporter line for monitoring chemical-induced cardiotoxicity. Issue 3 (7th June 2019) - Tsai, Su-Yi; Ghazizadeh, Zaniar; Wang, Hou-Jun; Amin, Sadaf; Ortega, Francis A; Badieyan, Zohreh Sadat; Hsu, Zi-Ting; Gordillo, Miriam; Kumar, Ritu; Christini, David J; Evans, Todd; Chen, Shuibing
Abstract: Aims : Human embryonic stem cells (hESCs) can be used to generate scalable numbers of cardiomyocytes (CMs) for studying cardiac biology, disease modelling, drug screens, and potentially for regenerative therapies. A fluorescence-based reporter line will significantly enhance our capacities to visualize the derivation, survival, and function of hESC-derived CMs. Our goal was to develop a reporter cell line for real-time monitoring of live hESC-derived CMs. Methods and results : We used CRISPR/Cas9 to knock a mCherry reporter gene into the MYH6 locus of hESC lines, H1 and H9, enabling real-time monitoring of the generation of CMs. MYH6:mCherry + cells express atrial or ventricular markers and display a range of cardiomyocyte action potential morphologies. At 20 days of differentiation, MYH6:mCherry + cells show features characteristic of human CMs and can be used successfully to monitor drug-induced cardiotoxicity and oleic acid-induced cardiac arrhythmia. Conclusion : We created two MYH6:mCherry hESC reporter lines and documented the application of these lines for disease modelling relevant to cardiomyocyte biology.